Ordinary Walking, Ordinary Writing: Some Thoughts in Preparation for an Essay as Yet Unwritten - Stead, Naomi (Writingplace, 2019)
Naomi Stead pursues a theoretical inquiry into the relationship between writing and walking based on author’s previous ficto-critical texts based in Stockholm, Sydney and Brisbane. The text was inspired by a small article that appeared in the daily newspaper in Melbourne, Australia in March 2018, which described the effect of different linguistic formulations used by phone dispatchers at ambulance stations, when someone telephoned in need of urgent medical attention. The story was about the difference between the dispatcher asking ‘what happened’ – which tended to send the caller off into a longwinded narrative account with much extraneous detail – and when the dispatcher asked ‘what’s happened’ – which caused the caller to report, quickly and directly, the sequence of events that had led to the medical emergency. The difference between these two modes of communication – the division of ‘what’ and ‘what’s,’ the single letter – was measured in long seconds, even minutes, and could easily be the difference between life and death. This text is introduced by a reading compiled by Robin Wilson